A NOVEL SOLUTION FOR BANKING SECTORS TO MAKE SECURE TRANSACTION USING BLOCK CHAIN TECHNOLOGY (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Effective information retrieval system in hospital is a web app which can be used in hospitalsto upload patient details. Using this web app upload patient details for first time and generate a user ID forthe particular patient for center use also. This user ID can be used by the patient for later use in anyhospital which are linked by this web app. The proposed web app can reduce the time for the patients andthe hospital workers for center use. Also, this web app can be used in any hospitals if the patient had auser ID. In this web app we provide security using Advanced Encrypted Standard algorithm. Our majorgoal is to link many hospitals in a single web app and to provide the details similarly. The proposed webapp provides user ID for the patients and it is easier to break anywhere.